Effect of die coating on surface crack depth of hot extruded 7075 aluminum alloy - Tatsuya Funazuka; Kuniaki Dohda; Norio Takatsuji; Chengliang Hu; Ngernbamrung Sukunthakan (Friction, 2022)
Abstract The aluminum alloys belonging to the 7000 series are high-strength alloys used in a wide variety of products for weight reduction. They are primarily used in the field of transportation and aerospace. Among these, the A7075 alloy has the highest strength and is expected to be applicable in a wide range of fields, such as aircraft components and sports equipment. However, it has high deformation resistance and is prone to surface defects, which is called tearing. Tearing typically occurs at high temperatures and high ram speeds, and adversely affects productivity. The localized melting of Zn and additive compounds, due to the heat generated during the process, is considered to cause tearing. In this study, the effect of friction, heat, and tearing at the tool—metal interface was mitigated by improving the die surface quality. The reduced friction eliminated recrystallization by preventing the temperature from increasing to recrystallization temperature. In addition, an AlCrN coating was adopted instead of nitriding to improve the die surface quality. The tearing size and heat generated when using the AlCrN coating were found to be limited. Moreover, the grain size observed in the tearing region on the extruded surface was small. The simulations using the shear friction coefficient m observed from friction tests indicate that the use of the AlCrN coating improved the material flow. Thus, the AlCrN coating is considered effective for reducing friction at the interface and preventing the recrystallization of the extruded surface. From the aforementioned results, it can be inferred that a die coating can reduce the tearing sensitivity and increase the productivity of the A7075 alloy.